Magnetic and near-infrared-II fluorescence Au–Gd nanoclusters for imaging-guided sensitization of tumor radiotherapy. Issue 7 (17th March 2022) - Zhao, Hui; Wang, Hao; Li, Hairu; Zhang, Tiecheng; Zhang, Jing; Guo, Wenhui; Fu, Kuang; Du, Guoqing
Abstract : Ultrasmall Au–Gd NCs with high-Z elements were used to perform dual-modal (NIR-II fluorescence and MRI) imaging-guided sensitization of tumor radiotherapy. Abstract : The significant role of multifunctional nanoprobes with complementary advantages in magnetic and near-infrared-II (NIR-II, 1000–1700 nm) fluorescence properties has been documented in precision cancer theranostics. However, certain limitations, including the large size (>10 nm), low NIR-II fluorescence quantum yield (QY < 1.0%), and inefficient magnetic performance (relaxation rate < 5.0 s −1 mM −1 ) of nanoprobes, restrict their biomedical applications and clinical translation. Albumin-based biomineralization was adopted to prepare bright NIR-II Au NCs, which were further conjugated with DTPA and Gd ions to produce magnetic and NIR-II Au–Gd NCs. Albumin-based biomineralization helped to develop ultrasmall Au–Gd nanoclusters with ultrasmall size (∼2 nm), high NIR-II fluorescence QY (∼3.0%), and effective magnetic resonance imaging (MRI) performance (relaxation rate (r1) = 22.6 s −1 mM −1 ). On the one hand, Au–Gd NCs achieved NIR-II fluorescence and MRI dual-modal imaging of tumors with a high signal-to-background ratio (SBR = 8.2) in mice. On the other hand, their effective metabolism simultaneously through the kidney and liver minimized their toxicity in vivo . Moreover, compared to the control group, the survival time of tumor-bearing mice was extended by three times when Au–Gd NCs with high-Z elements were used to perform dual-modal imaging-guided sensitization of tumor radiotherapy. Thus, ultrasmall nanoprobes with complementary imaging modalities and therapeutic functions manifest great potential in cancer precision diagnosis and therapy.